Cover Feature: Fusing Carborane Carboxylic Acids with Alkynes: 3D Analogues of Isocoumarins via Regioselective B−H Activation (Chem. Eur. J. 3/2018). Issue 3 (2nd November 2017) - Lin, Furong; Shen, Yunjun; Zhang, Yuanbin; Sun, Yuji; Liu, Jiyong; Duttwyler, Simon
Abstract : The preparation of a new class of heterocycles is reported. Fusion of carborane carboxylic acids with alkynes leads to three‐dimensional bora‐analogues of isocoumarins. The procedure relies on an iridium‐catalyzed alkenylation/annulation sequence between monocarba‐ closo ‐dodecaborate clusters and diarylacetylenes. Regioselective B−H activation, followed by B−C bond formation and ring closure, affords the fused cyclized products. More information can be found in the Communication by S. Duttwyler et al. onpage 551 .